READINESS TO CHANGE AND INNOVATIVE BEHAVIOR AS A DRIVEN OF SUSTAINABLE INNOVATION IN THE RURAL BANK AND SHARIA RURAL BANK INDUSTRY - Muhammad Ras Muis; Prihatin Lumbanraja; Isfenti Sadalia; Yeni Absah (Proceeding International Seminar of Islamic Studies, 2022)
The success of innovation in the rural bank and shariah rural bank industry lies in the quality of human resources. Employees' abilities related to readiness to change and innovative behavior affect team innovation. The rapidly changing times must be anticipated by the Management and Employees of rural bank and shariah rural bank with quality innovations. The concept of team innovation will provide views and guidance for employees to be able to improve the competitiveness and existence of rural bank and shariah rural bank, now and in the future.Keywords: readiness to change, innovative behavior, synergizing teamwork and team innovation.